Why do women seek ultrasound scans from commercial providers during pregnancy? - Roberts, Julie; Griffiths, Frances E.; Verran, Alice; Ayre, Catherine (Wiley, 2015)
The commercial availability of ultrasound scans for pregnant women has been controversial yet little is known about why women make use of such services. This article reports on semi-structured interviews with women in the UK who have booked a commercial scan, focusing on the reasons women gave for booking commercially provided ultrasound during a low-risk pregnancy. Participants’ reasons for booking a scan are presented in five categories: finding out the sex of the foetus; reassurance; seeing the baby; acquiring keepsakes and facilitating bonding. Our analysis demonstrates that women's reasons for booking commercial scans are often multiple and are shaped by experiences of antenatal care as well as powerful cultural discourses related to ‘good’ parenting and the use of technology in pregnancy. Sociological and public debate about the availability of commercial ultrasound and its social and personal impacts should consider the wider sociocultural context that structures women's choices to make use of such services.